Dynamics models of flexible aircraft - Yogeshwaran Jayaraman (2014)
Recent trends in aircraft design owing to requirements of high performance and weight reduction have resulted in aircraft possessing significant structural flexibility. Under these conditions, flight vehicles become vulnerable to unfavourable interactions between the structural dynamics of flexible components, aerodynamics and the overall motion of the body. In order to utilize automatic flight control systems to mitigate these effects, integrated flight models that account for the internal dependencies in the system must be developed. To this end, this work presents the derivation of flight models describing the dynamics of flexible aircraft. The equations are expressed in compact matrix-vector form, suitable for integration with state-space control systems. The dynamics of elastic bodies are first discussed, followed by numerical simulation results of a slender beam undergoing a spin-up maneuver. Finally, the equations governing the dynamics of flexible aircraft are derived and simplifications to obtain lower complexity models are discussed. The formulation is demonstrated through an example aircraft and some preliminary simulation results are presented. It is hoped that the integrated dynamics models derived in this work can be used for control design, flight simulation, parameter estimation and other studies, which are traditionally performed on six degree-of-freedom rigid-body flight models.